2018
DOI: 10.2494/photopolymer.31.209
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Underlayers in EUVL

Abstract: There is a growing awareness that underlayers (UL) are important in EUV lithography (EUVL). In previous lithography generations ULs were required to overcome reflectivity, however that is not a concern in EUVL. Nevertheless, surface interactions are becoming prevalent because the different layers of the stack are becoming thinner. This work focuses on the influence of the spin on carbon (SOC) layer used to print line-space patterns with metal containing resists (MCR). A significant impact of underlayers on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Moreover, this interfacial layer may also affect the homogeneity of resist additives, such as the photoacid generator (PAG) and quencher, which most certainly will affect the resist patterning performance. This sensitivity might also partially explain the differences in patterning behavior of EUV resists on different substrates [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this interfacial layer may also affect the homogeneity of resist additives, such as the photoacid generator (PAG) and quencher, which most certainly will affect the resist patterning performance. This sensitivity might also partially explain the differences in patterning behavior of EUV resists on different substrates [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this interfacial layer may also affect the homogeneity of resist additives, such as the photoacid generator (PAG) and quencher, which most certainly will affect the resist patterning performance. This sensitivity might also partially explain the differences in patterning behavior of EUV resists on different substrates [7]. Since the previous section indicated that the polymer film was sensitive to the substrate, two relevant commercial patterning spin-on underlayers (organic and inorganic) were tested to assess the impact of different underlayers on the Tg.…”
Section: Euv Patterning Performance Of the Full Resist Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been very well documented that under EUV exposures, the presence of ULs affects significantly the performance of the resists [7]. This is mainly happening due to the fact that very thin photoresists layers are now used; that means that interactions at the interface of resist and UL will have a much larger impact on the photoresist compared to exposures done at other wavelengths.…”
Section: Underlayersmentioning
confidence: 99%
“…4. Recently, improvement of lithography performance by using underlayer was reported and certain underlayer improved not only sensitivity but also nano-scale defect resistance [12]. A zinc organic cluster resist was evaluated on different underlayer with NXE tool at imec and the results are summarized in Fig.…”
Section: Zr Organic Cluster Zr Oxide Nanoparticlementioning
confidence: 99%